Relevance of morphological features for hepatocellular adenoma classification in pathology practice - Carla Henriques Agostini; Osmar Damasceno Ribeiro; Arlete Fernandes; Adriana Caroli-Bottino; Vera Lucia Pannain (BMC, 2020)
Abstract Background Gene mutations correlated with histological and immunohistochemical phenotypes of hepatocellular adenoma were recently identified. Based on these findings, four adenoma subtypes were distinguished. We classify hepatocellular adenoma (HCA) into subtypes based on histologic and immunohistochemical findings and verify the contribution of histological features in pathology practice. Methods Thirty hepatocellular adenomas were classified in subtypes. Sinusoidal dilatation, ductular reaction, pseudoportal tracts, pseudoglands, steatosis, inflammatory infiltrate and cellular atypia were analyzed, as well as liver fatty acid binding protein, β catenin, serum amyloid A, glutamine synthetase, and C-reactive protein antibodies. Results Histologically, eleven adenomas were classified as HNF1A inactivated (HHCA), five were β-catenin-activated (bHCA) and fourteen were inflammatory adenoma (IHCA). Steatosis was found in all HHCA and was predominantly severe. Sinusoidal dilatation and inflammatory infiltrate were present in all IHCA. Ductular reaction, pseudoportal tracts and cellular atypia were observed in 71.4, 85.7 and 42.8%, respectively. Pseudoglands were present in 60% and cellular atypia in 80% of bHCA. According to immunohistochemistry, 11 were HHCA; 1 was bHCA; 17 were IHCA, among which 5 were β-catenin activated IHCA; and 1 was unclassified UHCA (UHCA). Superior concordance between the histological and immunohistochemical classifications was found for HHCA (К = 0.854) and IHCA (К = 0.657). Conclusion Approximately 90% of adenomas may be diagnosed by subgroup based only on morphological features. When aberrant β catenin nuclear staining is not found, glutamine synthetase positivity is useful for diagnosis, although supplementary molecular analysis may be necessary.